Versatile cleaning service robot based on a mobile manipulator with tool switching for liquids and garbage removal in restrooms. (17th September 2022) - Wakayama, Tatsuhiro; Fujiura, Eri; Yamaguchi, Mari; Yoshida, Naoki; Inoue, Tomoaki; Ikeuchi, Hiroki; Yamamoto, Masaki; El Hafi, Lotfi; Garcia Ricardez, Gustavo A.; Takamatsu, Jun; Taniguchi, Tadahiro; Ogasawara, Tsukasa
Abstract : In recent years, the labor shortage has become a significant problem in Japan and other countries due to aging societies. However, service robots can play a decisive role in relieving human workers by performing various household and assistive tasks. Restroom cleaning is one of such challenging tasks that involve performing motion planning in a constrained restroom setting. In this study, we propose a mobile manipulator to perform various tasks related to restroom cleaning. Our key contributions include system integration of multiple tools on an arm with high DoF mounted on a mobile, omni-directional platform capable of versatile service cleaning and with extended reachability. We evaluate the performance of our system with the competition setting used for the restroom cleaning task of the Future Convenience Store Challenge at the World Robot Summit 2020, where we obtained the 1st Place. The proposed system successfully completed all the competition tasks within the time limit and could remove the liquid with a removal rate of 96%. The proposed system could also dispose of most garbage and got an average garbage disposal rate of 90%. Further experiments confirmed the scores obtained in the competition with an even higher liquid removal rate of 98%. GRAPHICAL ABSTRACT: UF0001